Islamic corporate governance and performance based on maqasid sharia index– study in Indonesia - Hasan Mukhibad; Mahameru Rosy Rochmatullah; Warsina Warsina; Rahmawati Rahmawati; Doddy Setiawan (Jurnal Siasat Bisnis, 2020)
Sharia banks and conventional banks have real differences in their objectives and operations. Therefore, performance measurements must differentiated between Sharia banks and conventional banks. One performance measure recommended by researchers is performance-based on the Maqasid sharia Index (MSI). This study is to prove the influence of the Sharia Supervisory Board attributes (number of meetings, level of education, cross-membership) and commissioners' attributes (ratio of independent commissioners, number of members, number of meetings) to performance based on MSI. The research sample is 12 Sharia banks in Indonesia during the 2014-2018 observation year. The data analysis method uses panel data analysis with a fixed effect model. We find that SSB education level and independent board ratio had a negative effect on performance based on MSI. Cross-membership; the number of SSB meetings, board size, number of board meetings, and total assets does not affect performance based on MSI. This finding indicates that MSI has not become one of the goals that must be achieved in the management of Sharia banks in Indonesia. This is because the MSI score is still low. In addition, the dominance of debt financing is a characteristic that banks prefer transactions that generate fixed income and avoid transactions that use a fairer system, i.e. the Profit and Loss Sharing system. We recommend for regulators to develop different measurement tools from conventional banks and in accordance with the objectives of sharia implementation as sharia bank business operations (maqasid sharia). Future researcher can study and develop other measurement tools in formulating maqasid sharia by involving regulators, business actors, and experts so that the produced maqasid sharia indicators can be applied by banks.